A randomized phase 3 trial of the immunogenicity and safety of coadministration of a live-attenuated tetravalent dengue vaccine (TAK-003) and an inactivated hepatitis a (HAV) virus vaccine in a dengue non-endemic country. Issue 7 (10th February 2023) - Tricou, Vianney; Eyre, Susannah; Ramjee, Mahadev; Collini, Paul; Mojares, Zenaida; Loeliger, Edde; Mandaric, Sanja; Rauscher, Martina; Brose, Manja; Lefevre, Inge; Folschweiller, Nicolas; Wallace, Derek
Highlights: Seroprotection from HAV vaccine was not impaired by coadministration with TAK-003. Immunogenicity of TAK-003 was not impacted by coadministration with HAV vaccine. Both vaccines, alone or concomitantly, were well tolerated by trial participants. Overall, these results support the coadministration of HAV vaccine and TAK-003. Abstract: Background: Vaccination against hepatitis A virus (HAV) is largely recommended for travelers worldwide. Concurrent dengue and HAV vaccination may be desired in parallel for travelers to countries where both diseases are endemic. This randomized, observer-blind, phase 3 trial evaluated coadministration of HAV vaccine with tetravalent dengue vaccine (TAK-003) in healthy adults aged 18–60 years living in the UK. Methods: Participants were randomized (1:1:1) to receive HAV vaccine and placebo on Day 1, and placebo on Day 90 (Group 1), TAK-003 and placebo on Day 1, and TAK-003 on Day 90 (Group 2), or TAK-003 and HAV vaccine on Day 1, and TAK-003 on Day 90 (Group 3). The primary objective was non-inferiority of HAV seroprotection rate (anti-HAV ≥ 12.5 mIU/mL) in Group 3 versus Group 1, one month post-first vaccination (Day 30) in HAV-naïve and dengue-naïve participants. Sensitivity analyses were performed on combinations of baseline HAV and dengue serostatus. Secondary objectives included dengue seropositivity one month post-second vaccination (Day 120), HAV geometric mean concentrations (GMCs), and safety. Results: 900 participants were randomized. On Day 30, HAV seroprotection rates were non-inferior following coadministration of HAV and TAK-003 (Group 3: 98.7 %) to HAV administration alone (Group 1: 97.1 %; difference: −1.68, 95 % CI: −8.91 to 4.28). Sensitivity analyses including participants who were neither HAV-naïve nor DENV-naïve at baseline supported this finding. Anti-HAV GMCs on Day 30 were 82.1 (95 % CI: 62.9–107.1) mIU/mL in Group 1 and 93.0 (76.1–113.6) mIU/mL in Group 3. By Day 120, 90.9–96.8 % of TAK-003 recipients were seropositive (neutralizing antibody titer > 10) to all four dengue serotypes. Coadministration of HAV vaccine and TAK-003 was well tolerated, with no important safety risks identified. Conclusion: Immune responses following coadministration of HAV vaccine and TAK-003 were non-inferior to administration of HAV vaccine alone. The results support the coadministration of HAV vaccine and TAK-003 with no adverse impact on immunogenicity, safety, and reactogenicity of either vaccine. ClinicalTrials.gov registration: NCT03525119.